“I have dropped out three times”: why young people in Ethiopia often repeat years in school - Tafere, Y; Tiumelissan, A (Young Lives, 2021)
This policy brief draws on qualitative research relating to young people in five communities (both rural and urban) who are part of the Young Lives longitudinal study of 3,000 children and young people in Ethiopia.